Technology assessment in patent search engine: An effort for reading invention opportunities and product innovation - Ferianto, Ferianto; Ariyani, Luthfina; Hendrix, Tommy (BISMA (Bisnis dan Manajemen), 2022)
Examining the technology opportunities of the patent search engine through technology assessment can help the companies determine the appropriate direction of further technology development to open-up business opportunities in the future. This paper aims to conduct a technology assessment on patent search engine technology to understand the trends of patent search engine development. This study used a qualitative research methodology with descriptive analysis according to literature studies and patent analysis. Innography software was used to derive the patent data. The results showed the technology development trend, key players involved, and the competitors related to patent search engine technology. The analysis has been conducted on IPRs data of 38 registered in patent search engine fields to identify several aspects, such as inventor, organisation, IP class, filling year, patent strength and factor, portfolio strength, and GEM finder. The patent database becomes an asset to define many technical processes from research and development. Conducting patent analysis in patent search engines is essential to capture opportunities for invention and innovation in related field technology.